Site-directed mutagenesis reveals the importance of conserved charged residues for the transport activity of the PheP permease of Escherichia coli. - Pi, J (1993)
Site-directed mutagenesis has been used to identify a number of charged residues essential for the transport activity of the PheP protein. These residues are highly conserved in the cluster of amino acid transporters. However, some other conserved residues and a number of aromatic residues have been shown not to be essential for transport activity.